Milk yield of East African, Galla, their first crosses (F1) with Toggenburg and Anglonubian and the 4-way dual purpose goats (DPG) under station management - Mwandotto, B.A.J.; Ahuya, C.O.; Mkuu, S.; Taylor, J.F.; Ruvuna, F. (1991)
Lactation and mean daily yields of 71 does comprising the synthetic dual purpose 4 way crosses, Fl's and the indigenous Galla and East African (EA) were analysed using general linear models to identify main variables influencing these characters and to evaluate the management at the Olmagogo station. Both breed and season of kidding had highly significant (p.05). Age of dam at kidding approached significance in influencing lactation yields. The 4-way crosses had the highest and the EA the lowest yields. However the greatest improvement in yields was in the FI indicating that while the greatest effect of crossbreeding in milk yields was at the Fl level, further improvement in developing the DPG will come through intensive selection. Animals kidding in the wet season tended to have higher lactation yields than those kidding in the dry season. Generally animals showed a long productive longevity especially the indigenous does. To adequately quantify the merits of the indigenous animals more work will be done on the comparative fertility and productivity levels. The study suggests that as the potential for long and high lactation does is established at Olmagogo by breeding the DPG, the management has also to develop a dry season package to sustain the yields. The indicated seasonal breeding will have to be judged against the demand for continuous supply of milk to the farm family and the need to reduce kid mortality when group kidding occurs especially during rainy seasons.